2018
DOI: 10.18632/oncotarget.25268
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in DNA mismatch repair pathway genes predict toxicity and response to cisplatin chemoradiation in head and neck squamous cell carcinoma patients

Abstract: Head and neck squamous cell carcinoma (HNSCC) is treated with cisplatin (CDDP) and radiotherapy (RT), and distinct results are observed among patients with similar clinicopathological aspects. This prospective study aimed to investigate whether MLH1 c.-93G>A (rs1800734), MSH2 c.211+9C>G (rs2303426), MSH3 c.3133G>A (rs26279), EXO1 c.1765G>A (rs1047840), and EXO1 c.2270C>T (rs9350) single nucleotide polymorphisms (SNPs) of the mismatch repair (MMR) pathway change side effects and response rate of 90 HNSCC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 45 publications
(54 reference statements)
3
44
3
1
Order By: Relevance
“…Zhu et al [27] recently observed that the rs2303428 genotype was an independent prognostic factor in hepatocellular carcinoma. Two other studies, however, failed to show an association of this polymorphism with prognosis and/or chemoradiotherapy response in rectal cancer and head and neck squamous cell carcinoma [28,29]. Together with our results relating its positive correlation with GC outcome, these findings may indicate a tumor type-dependent effect for this polymorphism.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Zhu et al [27] recently observed that the rs2303428 genotype was an independent prognostic factor in hepatocellular carcinoma. Two other studies, however, failed to show an association of this polymorphism with prognosis and/or chemoradiotherapy response in rectal cancer and head and neck squamous cell carcinoma [28,29]. Together with our results relating its positive correlation with GC outcome, these findings may indicate a tumor type-dependent effect for this polymorphism.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, some genetic defects may impact MMR function or activity other than MMR protein expression level [15]. Specifically, common polymorphisms of MMR genes with a low-penetrant effect that may be also insufficient to induce MSI can cause heterogeneous MMR capability among individuals, which correlates with cancer risk and clinical outcome [16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…37 MSH3 GG or GA and GT haplotype of EXO1 rs1047840 and rs9350 SNPs predisposed patients to significantly greater probability of pronounced ototoxicity from cisplatin than MSH3 AA genotype and other EXO1 haplotypes, respectively. 32 Genetic changes associated with better hearing outcomes have also been reported. Genes and SNPs related to protection against cisplatin ototoxicity include GSTM3 (rs1799735), GSTM1 null, GSTP (rs1695), SLC16A5 (rs4788863), OTOS (rs77124181; rs2291767), and OCT2 (rs316019).…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…Risk factors include young age (children under 5 years of age), 27,28 male children, 29 elderly patients, cumulative dose > 400 mg/m, 2,27 noise exposure, 30 combination with other ototoxic drugs 31 including carboplatin, 32 nutritional depletion and anemia, 33 cranial irradiation, 31 and genetic predisposition (pharmacogenomics).…”
Section: Risk Factors For Ototoxicitymentioning
confidence: 99%
“…The p.E216K mutation in POLB does not alter polymerase activity in vitro [15], but it has cellular effects in vivo (manuscript in preparation). The p.E589K mutation in EXO1 has been reported to affect the response to cisplatin treatment in patients with head and neck tumors [34], and thus may also be functional. Furthermore, all tumors with a Gleason score >7 contained either the p.E216K POLB mutation or a prevalent missense mutation in EXO1 (p.E589K, p.V458M, or p.H354R).…”
Section: Discussionmentioning
confidence: 99%